NEW METHODS OF TEACHING: FLIPPED CLASSROOM MODEL - Kurbaniyazova, S. (ILIM hám JÁMIYET, 2025)
The article explores the flipped classroom model, its principles, and implementation strategies, supported by scholarly views from prominent methodologists. Additionally, a practical experiment is discussed, demonstrating the implementation of the new approach in the English language classroom. The experiment serves to illustrate how the model can enhance student engagement, promote active learning, and provide more personalized instruction.